Knowledge and beliefs about behavioral biases - Jürgen Huber; Michael Kirchler; Teresa Steinbacher (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2024)
In this study we explore the knowledge and beliefs regarding behavioral biases among behavioral scientists, financial professionals, and the general population. We investigate knowledge about ten prominent biases and collect beliefs about the knowledge levels of each of these subject pools by conducting an online survey with 547 participants. We find that knowledge about the selected biases is highest among behavioral scientists and lowest in the general population. Potential explanatory variables, such as age, gender, income, and financial literacy, show almost no impact on knowledge levels. Regarding accuracy of beliefs about knowledge of the own and the other groups, each subject pool has the highest accuracy rates for their own group, and behavioral scientists assessing other behavioral scientists have by far the highest accuracy rate.
Keywords: C91; G40; G53; 330; Behavioral biases; expert beliefs; behavioral scientists; financial professionals